Does Movement Matter? Prefrontal Cortex Activity During 2D vs. 3D Performance of the Tower of Hanoi Puzzle - Kimberly Milla; Kimberly Milla; Elham Bakhshipour; Elham Bakhshipour; Barry Bodt; Nancy Getchell; Nancy Getchell (Frontiers in Human Neuroscience, 2019)
In the current study, we used functional near-infrared spectroscopy (fNIRS) to compare prefrontal cortex (PFC) activity in adults as they performed two conditions of the Tower of Hanoi (ToH) disk-transfer task that have equivalent executive function (EF) but different motor requirements. This study explored cognitive workload, here defined as the cognitive effort utilized while problem-solving by performance output. The first condition included a two-dimensional (2D) computerized ToH where participants completed trials using a computer mouse. In contrast, our second condition used a traditional, three-dimensional (3D) ToH that must be manually manipulated. Our aim was to better understand the role of the PFC in these two conditions to detect if PFC activity increases as a function of motor planning. Twenty right-handed, neurotypical adults (10M/10F, x¯ = 24.6, SD ± 2.8 years old) participated in two blocks (one per condition) of three 1-min trials where they were asked to solve as many puzzles as possible. These data were analyzed using a mixed effects ANOVA with participants nested within blocks for 2D vs. 3D conditions, presentation order (leading block), individual participants, and regions and additional follow-up statistics. Results showed that changes in oxygenated hemoglobin, ΔHbO, were significantly higher for 3D compared to 2D condition (p = 0.0211). Presentation order and condition interacted significantly (p = 0.0015). Notably, a strong correlation between performance and ΔHbO existed between blocks 1 and 2 (r = −0.69, r2 = 0.473, p < 0.01) when the 3D condition was initially performed, in contrast to the 2D condition where no significant correlation was seen. Findings also showed a significant decrease in ΔHbO between the first and second block (p = 0.0015) while performance increased significantly for both 3D and 2D conditions (p < 0.005). We plan to use this information in the future to narrow the potential points of impairment on the perception-cognition-action continuum in certain developmental disabilities.